Prevention of Diarrhea and Worms in Elementary School in the Pasirkaliki Health Center area, Bandung - Henny Cahyaningsih; Tjutju Rumijati; Ali Hamzah; Sri Kusmiati; Nursyamsiyah Nursyamsiyah; Metia Ariyanti; Sehabudin Salasa (Indonesian Journal of Community Development, 2022)
National health development is essentially the development of quality Indonesian people where one of the strategic efforts to improve a quality generation is through education and health through the School Health Business (UKS) program. The purpose of this community service is to improve the knowledge and skills of washing hand with soap (CTPS) properly in preventing diarrhea and worms in students at the Kresna and Jatayu State Elementary Schools in the Pasirkaliki Health Center , Bandung . The method used in this activity is participatory training and mentoring for school children through discussions, questions answers, demonstrations, and direct practice simulations in groups. The respondents who took part in this program were 40 elementary school students in grades 4 and 5 who were randomly selected. The results showed an increase in the average score before and after training for elementary school students, the average knowledge (1.7 to 2.83), and the average increase in skills (1.64 to 2.88). Elementary school students showed enthusiasm and were able to demonstrate how to wash hands with soap (CTPS). This activity needs to be followed up in collaboration with the Puskesmas to map out achievements in the implementation of training on the prevention of diarrhea and helminthiasis in primary schools in other Puskesmas.